2020
DOI: 10.1038/s41598-020-71028-4
|View full text |Cite
|
Sign up to set email alerts
|

Serum creatinine/cystatin C ratio as a case-finding tool for low handgrip strength in Chinese middle-aged and older adults

Abstract: Measuring handgrip strength is the initial step to diagnose sarcopenia. To investigate whether the serum creatinine (Cr)/cystatin C (CysC) ratio could serve as a case-finding tool for low handgrip strength, we conducted a diagnostic accuracy study. Adults (aged ≥ 40 years) with normal renal function were recruited. Trained nurses collected blood samples and conducted the anthropometric measurements and handgrip strength test. The serum concentrations of Cr, CysC, and other biomarkers were measured. We recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
9
1
Order By: Relevance
“…Our study showed that high normalized creatinine-to-cystatin C ratio reduced risk of diabetes in middle-aged and older adults. One might assume that this relationship is attributable to variations in muscle mass and/or muscle strength [5,6,18,28], both of which are identified determinants for risk of diabetes [20,29,30]. However, in the present study, the association between high normalized creatinine-to-cystatin C ratio and low risk of diabetes was independent of muscle strength.…”
Section: Interpretations and Implicationscontrasting
confidence: 59%
See 3 more Smart Citations
“…Our study showed that high normalized creatinine-to-cystatin C ratio reduced risk of diabetes in middle-aged and older adults. One might assume that this relationship is attributable to variations in muscle mass and/or muscle strength [5,6,18,28], both of which are identified determinants for risk of diabetes [20,29,30]. However, in the present study, the association between high normalized creatinine-to-cystatin C ratio and low risk of diabetes was independent of muscle strength.…”
Section: Interpretations and Implicationscontrasting
confidence: 59%
“…(2) were diagnosed with diabetes at baseline based on the American Diabetes Association 2010 criteria [21]; (3) had missing information on gender, body weight, body mass index (BMI), systolic blood pressure (SBP), or diastolic blood pressure (DBP); (4) were with outlier data (<1 or >99 percentile) on BMI, SBP, or DBP; (5) were with kidney disease or an estimated glomerular filtration rate (eGFR; calculated using the Chinesebased equation [22]) of less than 30 mL/(min×1.73 m 2 ); and (6) aged <45 years. Finally, a total of 5,055 middle-aged and older adults were included in this study (Supplementary Fig.…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of the creatinine to cystatin C ratio as a sign of low muscle mass was first proposed by Tetsuka [35], later called the sarcopenia index and validated among critically ill patients in intensive care units [36,37]. It was also clearly established that sarcopenia index is well correlated not only with muscle mass, but also with strength and markers of malnutrition and can serve as an objective tool for screening of malnutrition [23,38]. Taking into account the current diagnostic criteria for sarcopenia, these findings further support the utility of the creatinine/cystatin C ratio as a marker of sarcopenia.…”
Section: Discussionmentioning
confidence: 99%